Multiple Intelligences – in search of the birth of a theory - Dezső, Renáta Anna (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Professor Howard gardner received the 2020 Distinguished Contributions to Research in education Award, the premier honor from the American educational Research Association, AeRA. Gardner is best known for his theory of multiple intelligences, which suggests that human intelligence should be differentiated into modalities, rather than be accepted as a general ability. His theory has had a great infl uence on curriculum development as much as on everyday educational practice worldwide. The present study celebrates Gardner’s contribution to education sciences: it aims at analysing the context in which his theory was born, both in horizontal and verical dimensions. This overview offers a new alternative to the interpretation of the theory both to its sceptic and enthusiastic audience, as it presents the historical roots and the contemporary infl uences of the theory. The structure of effects and relationships introduced are that of the author, and leaves the fl oor open to different ways of interpretations, altering hermeneutical circles of the same topic. Besides the intentions introduced above, the present study intends to present the most signifi cant milestones of Gardner’s career for the Hungarian-speaking audience.